‘That’s Enough’ - Workplace Violence Against Physicians, Pharmacists, and Nurses in Saudi Arabia: A Systematic Review of Prevalence, Causes, and Consequences - Alhomoud F (Risk Management and Healthcare Policy, 2025)
Faten Alhomoud Department of Pharmacy Practice, College of Clinical Pharmacy, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Faten Alhomoud, Email falhomoud@iau.edu.saBackground: Workplace violence (WPV) threatens the safety and well-being of healthcare providers and leads to significant organizational consequences, including staff burnout, reduced productivity, and high turnover rates. At the societal level, it reduces the quality of care, increases medical errors, and imposes a substantial economic burden on healthcare systems and communities. Despite the global attention to WPV, systematic reviews specifically addressing WPV across all three professions—physicians, pharmacists, and nurses—and in various healthcare settings in Saudi Arabia are lacking. This review examines the prevalence, contributing factors, types, sources, potential causes, reactions, and impact of WPV against HCPs in Saudi Arabia.Methods: We conducted a systematic search of electronic databases from January 2010 to November 2024 and reviewed reference lists of included studies focusing on WPV against physicians, pharmacists, and nurses in Saudi Arabia. Two researchers independently screened studies for inclusion, resolved discrepancies through discussion, and extracted data in duplicate. The quality of included studies was assessed using critical appraisal tools for cross-sectional studies.Results: A total of 42 studies were reviewed using the AXIS tool for cross-sectional studies. The prevalence of WPV against HCPs ranged from 26% to 90.7%. This range reflects overall WPV prevalence across various studies, encompassing different healthcare settings and professional groups. Verbal violence was the most reported type (19.7– 98.2%), followed by threats (12– 74.4%), physical violence (3– 79%), and sexual violence (1.9– 76.5%). Perpetrators were predominantly male, with patients (7.1– 99.3%) and their relatives or friends (6.6– 91%) as the primary sources. Contributing factors of WPV included gender, age, profession, workload, shift patterns, nationality, experience, and inadequate training. Causes included staff shortages, overcrowding, long waiting times, miscommunication, unmet patient demands, insufficient penalties, and inadequate security measures. Responses to WPV varied, with some HCPs reporting incidents and others taking no action. The impact on HCPs included psychological distress, reduced work quality, and occasional job resignation.Conclusion: The high prevalence of WPV against HCPs in Saudi Arabia highlights the urgent need for enhanced protective measures, increased awareness of WPV policies, and improved reporting systems. Understanding the factors contributing to WPV can inform targeted intervention programs to foster safer healthcare environments.Keywords: health profession, healthcare worker, violence, workplace violence, review, Saudi Arabia